2017
DOI: 10.1038/ejcn.2017.24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin C supplementation on glycaemic control: a systematic review and meta-analysis of randomised controlled trials

Abstract: Randomised controlled trials (RCTs) have observed contrasting results on the effects of vitamin C on circulating biomarkers of glycaemic and insulin regulation. We conducted a systematic review and meta-analysis of RCTs testing the effect of vitamin C administration on glucose, HbA1c and insulin concentrations. Four databases (PubMed, Embase, Scopus and Cochrane Library) were used to retrieve RCTs published from inception until April 2016 and testing the effects of vitamin C in adult participants. The screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 46 publications
2
72
2
9
Order By: Relevance
“…8 Improvements in insulin sensitivity with AA supplementation may subsequently promote improvements in glycaemic control. Indeed, findings of some studies, 7,[9][10][11][12] but not others, 13 support the efficacy of AA supplementation in improving glycaemic outcomes, including lowering of HbA1c and fasting glucose concentrations in individuals with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…8 Improvements in insulin sensitivity with AA supplementation may subsequently promote improvements in glycaemic control. Indeed, findings of some studies, 7,[9][10][11][12] but not others, 13 support the efficacy of AA supplementation in improving glycaemic outcomes, including lowering of HbA1c and fasting glucose concentrations in individuals with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Excess lipid accumulation in adipose tissues is promoted by a number of transcription factors, including PPARγ, SREBP-1c, and members of the CCAAT/enhancer-binding protein family (Ntambi et al, 2000;Rosen and MacDougald, 2006;Tang and Lane, 2012). These master regulators of adipogenesis and lipogenesis function by inducing transcription of targets such as SCD1, FAS, and acetyl-CoA carboxy-lase (Rosen and MacDougald, 2006;Strable and Ntambi, 2010 -Wahab et al, 2002;Garcia-Diaz et al, 2014;Ashor et al, 2017). Moreover, Williams et al (2016) reported that dietary supplementation with vitamins E and C attenuates dexamethasoneinduced glucose intolerance in rats.…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, diabetic subjects likely have increased requirement of vitamin C. 11 Several clinical studies have alluded to the improvement of glycaemic control in diabetics with vitamin C supplementation. 12 Importantly, low levels of vitamin C were also observed in some TB patients, 13 and in a sizable population-based cohort study, adequate dietary intake of vitamin C has been suggested to protect against developing active TB in current smokers. 14 Thus, it appears rewarding to consider exploration of the potential benefit of supplementation of this micronutrient in preventing active TB in diabetic subjects.…”
Section: To the Editorsmentioning
confidence: 99%